2021
DOI: 10.1111/obr.13399
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic diets induce anxiety in rodents: A systematic review and meta‐analysis

Abstract: Obesity and mood disorders have been linked in a positive feedback loop. However, due to the bidirectional relationship between obesity and mental health, it is not clear whether anxiety is correlated with or caused by consumption of obesogenic diets.Here, we present a meta-analysis on the effects of dietary manipulation on rodent behavior in the elevated plus maze and open field test, the most common tests of anxiety-like behavior in animal models. The main dataset examined effects of obesogenic diets on time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…The relationship between obesity, diet, and anxiety is complex. While meta-analytic evidence suggests that obesogenic diets increase anxiety-like behaviour in the EPM and OFT in rodents consuming such a diet [60], here, we found anxiolytic effects of maternal Caf diet exposure in young offspring, regardless of whether these offspring were themselves fed a chow or Caf diet. Altered maternal care by Caf dams, maternal obesity-induced changes to offspring brain development, inflammatory changes, and maternal transfer of gut microbiota are among the mechanisms that may mediate behavioural changes in offspring [20,24].…”
Section: Discussioncontrasting
confidence: 77%
“…The relationship between obesity, diet, and anxiety is complex. While meta-analytic evidence suggests that obesogenic diets increase anxiety-like behaviour in the EPM and OFT in rodents consuming such a diet [60], here, we found anxiolytic effects of maternal Caf diet exposure in young offspring, regardless of whether these offspring were themselves fed a chow or Caf diet. Altered maternal care by Caf dams, maternal obesity-induced changes to offspring brain development, inflammatory changes, and maternal transfer of gut microbiota are among the mechanisms that may mediate behavioural changes in offspring [20,24].…”
Section: Discussioncontrasting
confidence: 77%
“…Zebrafish fed an obesogenic diet spent significantly less time in the low zone than control zebrafish during the anxiety tank tests (Figure 3b ); that is, these zebrafish were less “anxious” and displayed more exploratory behavior, in contrast to a finding by Ghaddar et al ( 2021 ). Rodent studies of diet‐induced obesity have also shown inconsistent results in exploratory behavior (Bracke et al, 2019 ; Zieba et al, 2019 ), although a recent meta‐analysis found obesogenic diets increased anxiety‐like behavior in elevated plus mazes as well as open field tests (Clark, Crean, & Senior, 2022 ). An increase in exploration is commonly associated with a “proactive” phenotype (Koolhaas et al, 2010 ; Øverli et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish fed an obesogenic diet spent significantly less time in the low zone than control zebrafish during the anxiety tank tests (Figure 3b); that is, these zebrafish were less "anxious" and displayed more exploratory behavior, in contrast to a finding by Ghaddar et al (2021). Rodent studies of diet-induced obesity have also shown inconsistent results in exploratory behavior (Bracke et al, 2019;Zieba et al, 2019), although a recent meta-analysis found obesogenic diets increased anxiety-like behavior in elevated plus mazes as well as open field tests (Clark, Crean, & Senior, 2022). An increase in exploration is commonly associated with a "proactive" phenotype (Koolhaas et al, 2010;Øverli et al, 2007).…”
Section: The Effect Of Obesogenic Diet On Anxietyrelated Behaviormentioning
confidence: 94%